Removal of Uranyl Ion from Wastewater by Magnetic Adsorption Material of Polyaniline Combined with CuFe2O4. (22nd April 2021) - Feng, Xinrui; Sun, Shaoshuai; Cheng, Ge; Shi, Lei; Yang, Xiangshan; Zhang, Yibo
Abstract : The magnetic adsorption material of polyaniline (PANI) with amino functional group combined with CuFe2 O4 (CuFe2 O4 /PANI nanocomposite) has been described in this work. It has been characterized by TEM, XRD, XPS, BET, FTIR, and VSM, respectively. Significantly, it exhibits extremely high maximum adsorption capacity (322.6 mg/g) for removal of uranyl ions from wastewater at a pH of 4. The adsorption process is consistent with the quasisecond-order kinetic equation, and the isotherm and kinetic data are accurately described by the Langmuir isothermal adsorption model. Furthermore, the magnetic CuFe2 O4 /PANI displays stable adsorption performance for uranyl ions after five cycles of recovery in acid medium, which indicates it possesses good recovery due to its magnetism and excellent regeneration ability for reusability.